Sexuality of Men: 3rd German Men’s Health Report (condensed version) - Foundation of Men’s Health (Psychosozial-Verlag, 2017)
We encounter the topic of sexuality everywhere: in films and books, in advertising, in press and on the internet. But how is the situation of sexual health in Germany? Although the scientific interest in masculine sexuality has grown over the last few decades, data that is reliable for many aspects is missing.The present Third Men’s Health Report, which was developed in collaboration with the Men´s Health Foundation and the Institute of Applied Sexual Studies at the Merseburg University of Applied Sciences, provides a current insight into the diverse facets of the sexuality of men from both social and medical perspectives. 40 experts from various disciplines have analysed in 31 contributions the level reached and they give extensive recommendations for action.With regard to questions of the social development of sexuality, the Men’s Health Report provides valuable information: How does sexuality develop in the 21st century? How do we avoid sexual discrimination based on sexual orientation? How can sexual offenses be further reduced?